Ion Manipulation from Liquid Xe to Vacuum: Ba-Tagging for a nEXO Upgrade and Future 0νββ Experiments - Dwaipayan Ray; Robert Collister; Hussain Rasiwala; Lucas Backes; Ali V. Balbuena; Thomas Brunner; Iroise Casandjian; Chris Chambers; Megan Cvitan; Tim Daniels; Jens Dilling; Ryan Elmansali; et al. (Atoms)
Neutrinoless double beta decay (<semantics>0νββ</semantics>) provides a way to probe physics beyond the Standard Model of particle physics. The upcoming nEXO experiment will search for <semantics>0νββ</semantics> decay in 136Xe with a projected half-life sensitivity exceeding <semantics>1028</semantics> years at the 90% confidence level using a liquid xenon (LXe) Time Projection Chamber (TPC) filled with 5 tonnes of Xe enriched to ∼90% in the <semantics>ββ</semantics>-decaying isotope 136Xe. In parallel, a potential future upgrade to nEXO is being investigated with the aim to further suppress radioactive backgrounds and to confirm <semantics>ββ</semantics>-decay events. This technique, known as Ba-tagging, comprises extracting and identifying the <semantics>ββ</semantics>-decay daughter 136Ba ion. One tagging approach being pursued involves extracting a small volume of LXe in the vicinity of a potential <semantics>ββ</semantics>-decay using a capillary tube and facilitating a liquid-to-gas phase transition by heating the capillary exit. The Ba ion is then separated from the accompanying Xe gas using a radio-frequency (RF) carpet and RF funnel, conclusively identifying the ion as 136Ba via laser-fluorescence spectroscopy and mass spectrometry. Simultaneously, an accelerator-driven Ba ion source is being developed to validate and optimize this technique. The motivation for the project, the development of the different aspects, along with the current status and results, are discussed here.